Cerebral Neoplasms in L-2 Hydroxyglutaric Aciduria: 3 New Cases and Meta-Analysis of Literature Data - Patay, Z.; Mills, J.C.; Löbel, U.; Lambert, A.; Sablauer, A.; Ellison, D.W. (American Journal of Neuroradiology, 2012)
SUMMARY: Increasing evidence suggests that patients with L2-HGA have a predisposition to cerebral neoplasms. This may be related to the pathologic accumulation of L2-HG because high amounts of 2-HG have been found in brain neoplasms that have IDH1 mutations. Our experience, on the basis of 11 previously unreported cases of L2-HGA, 3 of which developed cerebral neoplasms during the course of the disease, also supports an association between L2-HGA and cerebral neoplasms. We conducted a meta-analysis of published data, and we identified 295 patients (including our 11 patients) with L2-HGA. In 14 patients, the metabolic disorder was associated with cerebral neoplasms, suggesting an approximately 5% prevalence rate of CNS neoplasms in patients with L2-HGA; nonetheless, it may still be an underestimate. L2-HGA is an important disease “model” that provides further evidence to support the recently proposed pathogenetic role of 2-HG in the development of cerebral neoplasms. 2-HG2-hydroxyglutarateIDHisocitrate dehydrogenaseL2-HGL-2-hydroxyglutarateL2-HGAL-2-hydroxyglutaric aciduriaL2HGDHL-2-hydroxyglutarate dehydrogenaseMDHmalate dehydrogenasePNETprimitive neuroectodermal tumorWHOWorld Health Organization